Sovereign Bonds since Waterloo - Josefin Meyer; Carmen M. Reinhart; Christoph Trebesch (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper studies external sovereign bonds as an asset class. We compile a new database of 220,000 monthly prices of foreign-currency government bonds traded in London and New York between 1815 (the Battle of Waterloo) and 2016, covering 91 countries. Our main insight is that, as in equity markets, the returns on external sovereign bonds have been sufficiently high to compensate for risk. Real ex-post returns averaged 7% annually across two centuries, including default episodes, major wars, and global crises. This represents an excess return of around 4% above US or UK government bonds, which is comparable to stocks and outperforms corporate bonds. The observed returns are hard to reconcile with canonical theoretical models and with the degree of credit risk in this market, as measured by historical default and recovery rates. Based on our archive of more than 300 sovereign debt restructurings since 1815, we show that full repudiation is rare; the median haircut is below 50%.
Keywords: E40; F30; F40; G10; N00; 330; sovereign debt; default; risk premiums; investor returns; interest rates; portfolio; yields; coupons; recovery